TINJAUAN YURIDIS TERHADAP SANKSI DOUBLE TRACK SYSTEM DALAM SISTEM PERADILAN PIDANA ANAK - putri beta sona (Fakultas Hukum Universitas Malikussaleh, 2022)
Children are individuals who have not been fully responsible for their actions. So against children who are in conflict with the law, punishments are formed with the concept of a double track system as contained in Law Number 11 of 2012 concerning the Child Criminal Justice System. This article discusses how the concept of double track system sanctions against children is reviewed in juvenile justice. and discusses how the guidelines determine sanctions for juvenile justice children.